Ultrasonic arrays for monitoring cracks in an industrial plant at high temperatures - Kirk, K.J.; McNab, A.; Cochram, A.; Hall, I.; Hayward, G. (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 1999)
A piezoelectric linear array structure has been designed to operate at temperatures up to 400/spl deg/C for nondestructive testing of steel components of a hot industrial plant. It is intended that these arrays be fixed permanently to the test subject so that known defects can be monitored by comparing measurements taken over a period of time without needing to shut down the plant. The arrays are used in pairs: the transmitter is a phased array producing a variable angle steered beam, and a second array is used for receiving. The defect can be identified from a series of scans collected from individual elements of the second array. A simple monolithic array structure was used, based on a single crystal of lithium niobate and operating in the frequency range 3 to 5 MHz. Prototype devices have 64 elements on a 0.5 mm pitch. Simulated defects in steel blocks have been scanned at high temperatures to illustrate the arrays' capability for nondestructive testing. The results suggest an accuracy better than 1 mm in finding the location of crack tips.